PENGARUH BI RATE, INFLASI, KURS, DAN PDB RIIL TERHADAP DANA PIHAK KETIGA (DPK) SERTA DAMPAKNYA TERHADAP PEMBIAYAAN BERDASARKAN PRINSIP BAGI HASIL PADA PERBANKAN SYARIAH DI INDONESIA PERIODE 2009-2014 - Iswadi Iswadi (Universitas Islam Negeri Sumatera Utara, 2015)
Financial institutions, especially banking institutions have a strategic role for driving the economy of country. To give financing, the bank must obtain the fund in order to give the financing. There are two factors that affect the bank's ability to obtain funds from the public, namely internal and external factors. Internal factors that affecting in obtaining third-party funds are; bank products, interest rate policy, quality of service, the atmosphere of the office, location of offices, and the reputation of the office. While external factors, such as economic conditions, the activity and the condition of the government, the condition of money market, capital markets, government policies and regulations of Bank Indonesia.